When exercise does not pay : counterproductive effects of impending exercise on energy intake among restrained eaters - Sim, Aaron Y. (2019)
Evidence suggests people may overestimate the effectiveness of future positive behaviour, leading to counterproductive behaviours in the present. Applied to weight-management, we hypothesize that inaccurate expectations about impending exercise may impede weight management by promoting overconsumption prior to exercise. This study aimed to determine how expectations about impending exercise and its potential ability to expend energy may influence i) energy intake before exercise and ii) overall energy balance (energy intake minus energy expended via exercise). Using a randomised, counterbalanced design, 21 inactive, overweight males, following a baseline session, completed two experimental trials: i) ad-libitum snack meal (potato-crisps) followed by an exercise session (SE) and ii) ad-libitum snack meal only (SO). There was no main effect of condition (SE vs. SO) on ad-libitum snack intake (p = .917). However, after accounting for dietary restraint (covariate), a difference in snack intake between SE and SO was revealed (p = .050). Specifically, participants who scored higher in dietary restraint consumed more in the SE (vs. SO) session (162 ± 359 kcal more) compared with participants who scored lower in dietary restraint (89 ± 135 kcal less). Among restrained eaters, the relative (net) energy consumed after accounting for energy expended from exercise in SE was not different from the energy consumed in the SO condition, suggesting that energy expended via exercise in SE does not appear to negate extra energy consumed in this condition compared with SO. Of interest, desire to eat and prospective food consumption ratings at the start of the trial were greater (p ≤ .029) in SE compared with SO. Findings suggest that restrained-eaters are at risk of adopting compensatory eating behaviour that may impede negative energy balance typically resulting from exercise (i.e. expending insufficient energy to negate compensatory energy intake).